Penerapan Manajemen Risiko Berbasis ISO 31000 Pada Industri Otomotif Studi Kasus Bengkel Mentari Motor - Ari Assrishan Sosh Mantoro; Dea Wisnu Ramdani; Fajar; Fiqi Ardi Abdurahman Masdar; Alfiana (Indo Publishing, 2025)
This study analyzes the implementation of ISO 31000–based risk management at Bengkel Mentari Motor, an independent workshop in Bandung that has grown alongside increasing motorcycle ownership. Despite its business potential, the workshop’s risk management remains reactive and lacks a formal standard. A descriptive approach was used to identify risk types, assess risk levels, and determine appropriate mitigation strategies. The risks examined include operational, occupational safety, financial, equipment, service quality, and technological changes. The results show that several risks have high likelihood and impact, particularly those related to equipment condition, worker competence, and compliance with safety procedures. Based on the risk matrix, most risks fall into medium to high categories, requiring immediate control actions. The ISO 31000 framework provides a structured basis for identifying, analyzing, evaluating, and treating risks. The study recommends developing risk-based SOPs, enhancing mechanic training, implementing regular equipment maintenance, and establishing risk documentation to improve operational efficiency and business sustainability.